Bilingual Program Management Model for Enhancing Students’ Speaking Skills in a National Plus School - Kasari, Yulianie; Saydikramova, Umida Kh (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the implementation model of the bilingual class program and examine how its managerial structure contributes to improving students’ speaking skills in a national plus school context. Methodology: This research employed a qualitative descriptive case study design. Data were collected through structured classroom observations, semi-structured interviews, documentation analysis, and speaking performance assessment using an analytic scoring rubric (fluency, pronunciation, vocabulary, grammar, confidence). Data were analyzed using the interactive model of data reduction, display, and conclusion drawing with triangulation techniques. Main Findings: The findings show that systematic planning, structured teacher assignment, consistent English exposure, and continuous program evaluation significantly enhance students’ speaking fluency, vocabulary use, and communicative confidence. Functional bilingual interaction practices were more effective than symbolic language use in promoting active oral participation and contextualized language production. Novelty/Originality of this study: This study introduces an integrative managerial perspective linking bilingual program planning, organization, implementation, and evaluation with measurable speaking skill development. It advances existing bilingual education research by demonstrating that communicative competence improvement is strongly influenced by institutional management coherence, not solely classroom instructional techniques.